Systematic review of overactive bladder therapy in females - Cardozo, Linda (Canadian Urological Association Journal, 2013)
Although the prevalence of overactive bladder (OAB) is similar in both male and female populations, females have a greater tendency to seek medical advice regarding their symptoms. A review of the evidence of therapy among women shows that a variety of modalities has been shown to be effective for symptom improvement in women with OAB. Bladder retraining/re-education should be considered for all women with OAB. With respect to first-line pharmacotherapy with antimuscarinic agents, the development of extended release preparations, bladder selective M3 antagonists and alternative routes of delivery, have improved compliance and persistence. Other pharmacotherapeutic options with potential for providing benefit include antidepressants, vasopressin analogues, alpha-adrenoceptor antagonists and beta-adrenoceptor agonists. There are also a number of newer agents currently being investigated, including calcium channel blocking agents, potassium channel opening drugs, beta agonists and neurokinin receptor antagonists. Intravesical injections of botulinum toxin may be an alternative, while surgery can be considered for truly intractable cases.